An Investigation on the Dimensionality and Structure of Service Quality in Private Banks of South Odisha - Dash, Saroj Kumar; Choudhury, Snigdhamayee (Gyan Management Journal, 2021)
The success of any organization is measured in its ability to quickly respond to market changes with more efficient satisfaction and customer retention. The subject “quality” is nowadays, in a globalized world, one of the key concerns of businessmen to face the competition on industries and service areas. Financial groups are measuring no efforts to achieve quality excellence, starting by customer services and relationship. When the expression “Quality” is used, we usually think in terms of an excellent product or service that fulfills or exceeds our expectations. These expectations are based on the intended use and the selling price. Products are determined by its quality. Hence based on observation it is considered elusive. Quality can be quantified as Q = P/E. Where Q = Quality, P = Performance and E = Expectations. Quality is a complex phenomenon based on perceptions by individuals with different perspectives on products and services. These perceptions have been built up through the past experience of individuals and consumption in various contexts. Indian banking sector opened its doors to private and international players after the economic liberalization in 1991. It has been almost 2 decades of operation of the private banks in India. Much has evolved in the overall structure of banking during this time but have the private banks delivered the type of quality that the customers expect them to. This research is an effort to evaluate the service quality of the private banks in Southern parts of Odisha of the country India. The study is based on primary data collected in the cities of South Odisha through a structured questionnaire designed on the basis of SERVQUAL Model. The banks under study are the five top private banks from South Odisha region. The study has found that none of the banks have been able to meet the customer expectations and are still dwelling on the ‘zone of pain’. The research is very useful for managers, policymakers, implementers as well as academicians. The research provides implications for managers as well as policy makers to understand the customer expectations in India. It can be a guideline for a bigger role for the BCSBI (Banking Codes and Standard Board of India). Implications for future research are also discussed. The novelty of the research lies in the context that no effort has been made so far to effect research on sector specific contribution of banks. There is also very little literature available to identify the need-service gap in this area. The study adds value to the knowledge in the field of banking service quality for development and also opens new areas of research.